Management of root-knot disease of pointed gourd through the application of nematicides and different organic amendments - Akhter, B; Humaun, MR; Ahamed, KU (International Journal of Agricultural Research, Innovation and Technology, 2020)
A field experiment was conducted at Regional Agricultural Research Station, Bangladesh Agricultural Research Institute (BARI), Ishwardi, Pabna during 2013-14 to find out an effective integrated management package for controlling root knot nematode, Meloidogyne incognita of pointed gourd. The following treatments were T1 = Spore suspension of T. harzanium added to around the roots of seedling, T2 = Dry neem leaves @100 g seedling-1, T3 = Furadan 5G @ 40 kg ha-1, T4 = Poultry litter @ 5 t ha-1, T5 = Mustard oil cake @ 800 kg ha-1, T6 = Furadan 5G + Dry neem leaves, T7 = Furadan 5G + Poultry litter, T8 = Furadan 5G + Mustard oil cake and T9 = Control were tested for their performance against the disease. Gall index ranged from 3.33-7.67. Significantly lower gall index (3.33) was recorded in treatment T7= Furadan 5G + Poultry litter and maximum gall index (7.67) was recorded in treatment T9= Control plot. The highest yield (24.97 t ha-1) was recorded in Furadan 5G + Poultry litter treated plot where are the lowest yield (7.53 t ha-1) was in Control plot. The incorporation of Poultry litter with Furadan 5G increased the efficiency of the treatment and gave satisfactory result to reduce root knot disease and to improve plant growth and yield of pointed gourd. Int. J. Agril. Res. Innov. Tech. 9(2): 51-56, December 2019